Chemical and Process Plant Commissioning Handbook a Practical Guide to Plant System and Equipment Installation and Commissioning. - Killcross, Martin (Elsevier Science, 2011)
The Chemical and Process Plant Commissioning Handbook is a must have for engineers in the chemical process and process plant sectors, or for those refreshing their skills in this area. It provides a guide and reference to preparing a systematic methodology for converting a newly constructed plant, as well as streamlining equipment into an operational process unit. Includes downloadable commissioning process checklists that comply with industry standard best practice which readers can use and adapt for their own situations. The reference focuses on the critical safety assessment and inspection.
Includes index.
Keywords: Building commissioning -- Handbooks, manuals, etc.; Chemical plants -- Design and construction -- Handbooks, manuals, etc.; elektronické knihy; electronic books